Cognitive Aids Do Not Prompt Initiation of Cardiopulmonary Resuscitation in Simulated Pediatric Cardiopulmonary Arrests. Issue 1 (February 2018) - Nelson McMillan, Kristen; Rosen, Michael A.; Shilkofski, Nicole A.; Bradshaw, Jamie Haggerty; Saliski, Mary; Hunt, Elizabeth A.
Abstract : Introduction: Although American Heart Association guidelines exist for proper management of cardiopulmonary arrest (CPA), in-hospital cardiopulmonary resuscitation (CPR) may be of poor quality and is not performed in all indicated situations. Cognitive aids have been created to assist in rapid, accurate recall of guidelines for pediatric CPA management. Methods: Pediatric residents participated in individual mock codes for two years. Using a high-fidelity simulator, each resident participated in a standardized scenario that required management of both pulseless ventricular tachycardia and pulseless electrical activity. The primary study objective was to calculate the proportion of residents ( a ) who were not performing CPR on a simulated "pulseless" patient when cognitive aid use was first initiated and ( b ) who subsequently initiated CPR after cognitive aid use. Results: One hundred thirty-two (83.5%) of 158 pediatric residents participated, and of 125 videos available for review, 107 residents (85.6%) used a cognitive aid. Mean (SD) time to cognitive aid use was 106 (100) seconds after the mannequin became pulseless. Most common immediate actions prompted by cognitive aid use were the following: defibrillation, 43 (40%) of 107; and adrenaline (epinephrine) administration, 28 (26%) of 107. Most alarmingly, 58 (54%) of 107 were not performing CPR on the pulseless patient when cognitive aid use was initiated and only two (3.4%) of 58 were subsequently prompted to initiate chest compressions. Discussion: Cognitive aids in use during this study did not prompt timely initiation of CPR, potentially contributing to delays and errors in CPA management. Failure of these aids to prompt CPR initiation represents a "missed opportunity" to enhance performance of this vital skill.